Management of Leptomeningeal Metastases in Non-oncogene Addicted Non-small Cell Lung Cancer - Turkaj, Ana; Morelli, Anna M.; Vavalà, Tiziana; Novello, Silvia (Frontiers in Oncology, 2018)
Brain metastases in non-small cell lung cancer (NSCLC) patients are more often detected due to imaging modalities improvements but also emerge because of improved treatments of the primary tumor which lead to a longer survival. In this context, development of leptomeningeal metastases (LM) is a devastating complication and its prognosis remains poor despite advances in systemic and local approaches. Histology characterization of NSCLC and molecular expression influence LM management. For those with “oncogene addiction”, new generation epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKIs) were developed to strongly penetrate the blood-brain barrier (BBB) with the aim to prevent central nervous system cancer dissemination, eventually impacting on LM appearance and its subsequent management. Systemic chemotherapy, often combined with intrathecal chemotherapy (when possible), was one of common indications for lung cancer patients affected by LM, without driver mutations and a good performance status but currently, with the advent of innovative systemic approaches treatment solutions in this subgroup of patients are rapidly evolving. Whole brain radiation therapy (WBRT) is the conventional treatment for patients with brain metastases. Furthermore, modern radiation techniques, as stereotactic radiotherapy (SRT), improve outcomes in those cases with a limited number of lesions. However, LM represent a minority of CNS metastases and few literature data are available to drive the radiotherapy approach. Considering all relevant progress made in this setting, after a literature review, the aim of this paper is to discuss about recent developments and therapeutic options in LM management of non-oncogene addicted NSCLC.